2021
DOI: 10.3390/biomedicines9091111
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Tumor Cells: Technologies and Their Clinical Potential in Cancer Metastasis

Abstract: Circulating tumor cells (CTCs) are single cells or clusters of cells within the circulatory system of a cancer patient. While most CTCs will perish, a small proportion will proceed to colonize the metastatic niche. The clinical importance of CTCs was reaffirmed by the 2008 FDA approval of CellSearch®, a platform that could extract EpCAM-positive, CD45-negative cells from whole blood samples. Many further studies have demonstrated the presence of CTCs to stratify patients based on overall and progression-free s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 128 publications
0
39
0
Order By: Relevance
“…We consider these cells analogous to circulating tumor cells (CTCs). CTCs are a unique population of tumor cells that invade the basement membrane and intravasate into the vasculature, serving as the source of cells from which metastatic nodules will eventually form [ 26 ]. In this model, only those MDA-MB-231 cells that have the capacity to invade the basement membrane, intravasate into the zebrafish vasculature, and migrate using the circulatory system are monitored and studied.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We consider these cells analogous to circulating tumor cells (CTCs). CTCs are a unique population of tumor cells that invade the basement membrane and intravasate into the vasculature, serving as the source of cells from which metastatic nodules will eventually form [ 26 ]. In this model, only those MDA-MB-231 cells that have the capacity to invade the basement membrane, intravasate into the zebrafish vasculature, and migrate using the circulatory system are monitored and studied.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we used xenografted zebrafish embryos to identify two subpopulations of MDA-MB-231 breast cancer cells that exhibited progressively invasive behavior. These populations are analogous to circulating tumor cells found in human cancers [ 25 , 26 ]. Differential gene analysis of these subpopulations with their parental population revealed activation of an epithelial-mesenchymal transition (EMT) program as well as enrichment of several pathways consistent with prior reports of breast cancer metastasis.…”
Section: Introductionmentioning
confidence: 89%
“…The most widely reported and the only Food and Drug Administration (FDA)-approved technique to detect CTC and CTC cluster level was CellSearch™ System. CellSearch™ System (Menarini Silicon Biosystems Inc., Huntingdon Valley, PA, USA) is an antibody-based marker-dependent platform that applied immunomagnetic separation and flow cytometry protocol to detect CTCs in peripheral blood ( 58 ). No studies directly compare the sensitivity and specificity of different CTC detection methods.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that CTCs are an intermediate stage of cancer metastasis. Like ctDNA, CTCs are obtained from peripheral blood; however, CTCs may have a greater clinical impact as they can be grown, propagated, and extensively studied in vitro and in vivo under optimal conditions [ 208 , 209 ]. However, it is unclear if a single cell assay accurately reflects entire tumor heterogeneity.…”
Section: Molecular Profiling In the Bloodmentioning
confidence: 99%